PENGUATAN KOMITMEN ORGANISASI MELALUI KEBIJAKAN PENGEMBANGAN KARIR DAN PROFESIONALISME KARYAWAN - Arif Rachman Putra; Didit Darmawan (Jurnal Ilmiah Satyagraha, 2022)
One way to become a market leader is to have employees who havehigh abilities and are loyal to the organization where they work. This requirescooperation between employees, management, and company owners. Thiscooperation can occur if each party has a strong commitment to theorganization. Strengthening organizational commitment can be done bydeveloping factors that have a role in organizational commitment. The purposeof this study was to determine the effect of career development and employeeprofessionalism on organizational commitment. This quantitative research wasconducted at CV Anugerah Sidoarjo with a sample of 66 respondents. The studyused data then processed using SPSS with regression analysis. The resultsshowed that career development has a significant influence on the formation oforganizational commitment. In addition, organizational commitment is alsoinfluenced by the professionalism of employees. Together, career developmentand professionalism have a significant influence on organizational commitment.